1986
DOI: 10.1007/bf01644804
|View full text |Cite
|
Sign up to set email alerts
|

Ciprofloxacin pharmacokinetics in patients with cystic fibrosis

Abstract: The pharmacokinetics of ciprofloxacin were studied in cystic fibrosis patients and healthy volunteers following oral administration of 500 mg and 1000 mg. Serum kinetics as well as urinary recovery were monitored. As the body weights of cystic fibrosis patients and the healthy volunteers differed significantly, kinetic parameters were calculated on the basis of a constant relative dose in mg/kg body weight. Neither serum kinetics nor urinary recovery differed significantly between the two groups, as indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…Other investigators have reported mean bioavailabilities of 56 to 77% in normal volunteers (13,30,32), values which are not altered by administering ciprofloxacin with meals (17). (11,30) or those determined by a microbiological assay (3,4,6,12,22,32). This last finding is surprising in view of the fact that ciprofloxacin is metabolized to microbiologically active compounds that are eliminated in the urine (14 70-kg adult) (7) and is in good agreement with results obtained by other investigators (6,12).…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have reported mean bioavailabilities of 56 to 77% in normal volunteers (13,30,32), values which are not altered by administering ciprofloxacin with meals (17). (11,30) or those determined by a microbiological assay (3,4,6,12,22,32). This last finding is surprising in view of the fact that ciprofloxacin is metabolized to microbiologically active compounds that are eliminated in the urine (14 70-kg adult) (7) and is in good agreement with results obtained by other investigators (6,12).…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations of ciprofloxacin in lung tissue homogenates or ELF are as high as 15 to 29 mg/liter (Table 2) (144)(145)(146)(147)(148).…”
Section: Serum and Sputum Pharmacokineticsmentioning
confidence: 99%
“…In vitro exposure of P. aeruginosa to fluctuating enoxacin serum concentrations following oral doses of 500 mg/day administered either once or twice daily for 2 days resulted in rapid emergence of resistance due to the selection of moderately resistant subpopulations (243). A population analysis of four P. aeruginosa strains isolated from adult CF patients who were treated in 1983 for the first time in their lives with 500 mg ciprofloxacin orally twice daily (145) revealed that the preexposure isolates were heterogeneously susceptible to ciprofloxacin, with MICs for the subpopulations ranging from Յ1-to up to 16-fold the MIC of ciprofloxacin, as determined for the entire population by the CLSI method (97). These strains were exposed in vitro for 5 days to fluctuating ciprofloxacin concentrations simulating an oral 500-mg b.i.d.…”
Section: Emergence Of Resistance In Pk/pd Studies and In Cf Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a p-glycoprotein and active transport substrate in various drug disposition pathways (173,175,178,282). After an administration of a single oral dose (500mg), the AUC 0-∞ observed in Brazilian subjects was 1.5 to 4-fold smaller than that observed in German, Caucasian, US American, Indonesian and Chinese subjects (135)(136)(137)(138)(139)(140). A significantly higher ciprofloxacin AUC 0-∞ has been observed in Nigerian and Chinese compared with German subjects as well when administered intravenously (139,141,142).…”
Section: Fluoroquinolones -Ciprofloxacin Is Moderately Lipophilic Andmentioning
confidence: 99%